2019
DOI: 10.2478/ausal-2019-0004
|View full text |Cite
|
Sign up to set email alerts
|

Meat starter cultures: Isolation and characterization of lactic acid bacteria from traditional sausages

Abstract: Fermented meat products represent an important segment of our alimentation. Obtaining these products is based on beneficial microorganism activity. In the case of traditional food products, these are commercial starters or autochthonous microflora. Fermentation of raw materials is mainly done by sugar metabolization of lactic acid bacteria (LAB). In addition, these microorganisms can have other beneficial properties too such as probiotic properties, antimicrobial compound production abilities, etc. In order to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
1
7
1
Order By: Relevance
“…Greater zones of inhibition were observed against Gram-positive bacteria L. monocytogenes and S. aureus (Table 1). Lactic acid bacteria isolated from sausages by Laslo et al (2019) also showed an inhibitory effect against S. aureus (16.63 mm) and E. coli (14.47 mm), although with significantly smaller zones of inhibition than that found in this work.…”
Section: Antagonistic Activitycontrasting
confidence: 63%
See 3 more Smart Citations
“…Greater zones of inhibition were observed against Gram-positive bacteria L. monocytogenes and S. aureus (Table 1). Lactic acid bacteria isolated from sausages by Laslo et al (2019) also showed an inhibitory effect against S. aureus (16.63 mm) and E. coli (14.47 mm), although with significantly smaller zones of inhibition than that found in this work.…”
Section: Antagonistic Activitycontrasting
confidence: 63%
“…Gas production and acidification capacity were determined according to Laslo et al (2019). Capsule production was evaluated according to Hitchener et al (1982), through negative staining by the Gins method.…”
Section: Gas Production Acidification Capacity and Capsule Productionmentioning
confidence: 99%
See 2 more Smart Citations
“…In wild duck fermentation processes, S. succinus was the main species isolated. To our knowledge, this is the first time S. succinus has been reported in duck meat fermentation processes, although it has been found in other fermented meat products before [ 42 , 61 ]. This is not necessarily a matter of concern, but some strains of S. succinus exhibit proteolytic, lipolytic, and urease activities and can also be hemolytic and toxigenic [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 98%